Transglutaminase-catalysed cross-linking eliminates Penaeus chinensis tropomyosin allergenicity by altering protein structure - Linglin Fu (Food and Agricultural Immunology, 2019)
Transglutaminase (TG) is a major food processing enzyme that induces protein cross-linking. Tropomyosin (TM) is a major shellfish allergen that is responsible for at least 80% of the shrimp allergic incidents. The aim of this research was to investigate the effect of TG on TM allergenicity and reveal the involvement of TM structure alternation. After treated with TG for different time, the allergenicity of TM was assessed by indirect ELISA with shrimp allergic patients’ sera, and the structure of TM was characterized by circular dichroism (CD) spectroscopy, ultraviolet (UV) absorption spectroscopy and ﬂuorescence spectroscopy. Results showed that the allergenicity slightly decreased at the early stage of reaction and dramatically decreased at the late stage, which is tightly correlated with the increment of β-turn content and UV absorption. In conclusion, TG modification is an effective and promising food processing method to eliminate TM allergenicity with significant prospect of industrial application.